Reformas estructurales : mitos y realidades - Monreal Ávila, Ricardo, 1960- (Políticas Públicas., 2014)
Sharply critical analysis of Mexico's recent round of ambitious structural reforms, particularly of oil industry and finance reforms, which author says show direct line of descent from 18th-century Bourbon reforms, politics of Porfirio Diaz and neoliberal ideals of Carlos Salinas de Gortari, historical antecedents vilified by many on left in Mexico. Author was Mexico's youngest elected governor and is currently serving in Congress.